Peripartum and Postpartum Analgesia and Pain in Women Prescribed Buprenorphine for Opioid Use Disorder Who Deliver by Cesarean Section - Alane B O'Connor; Joel Smith; Liam M O'Brien; Kaitlyn Lamarche; Nadine Byers; Stephanie D Nichols (SAGE Publishing, 2022)
Aim: Little is known about whether pain can be effectively managed in pregnant women with opioid use disorder (OUD) during delivery hospitalization, particularly those undergoing surgery and taking buprenorphine as medication for OUD (MOUD). To address this question, we compared pain scores and opioid analgesic utilization during delivery hospitalization in women taking their pre-hospital dose of buprenorphine who delivered by cesarean section to matched controls. To inform future research efforts, we also began to explore opioid analgesic utilization and pain scores by type of anesthesia as this variable is often not included in related literature. Methods: Retrospective matched cohort study of 46 women prescribed buprenorphine during pregnancy who delivered by cesarean section during a 7-year period. Results: When compared to matched controls, women taking their pre-hospital dose of buprenorphine undergoing cesarean section utilized more opioid analgesics as measured by morphine milligram equivalents (MME) (mean MME first 48 hours 153.0 mg vs 175.1 mg, respectively, P  < .01) but had similar pain scores during delivery hospitalization. There was no difference in MME utilization by maternal dose of buprenorphine though sample sizes were small. Women on buprenorphine who received spinal anesthesia with morphine had mean pain scores that were 1.4 points lower ( P  = .01) during the first 48 hours than women on buprenorphine receiving other methods of anesthesia. Discussion And Conclusions: Pregnant women taking their pre-hospital dose of buprenorphine throughout their surgical delivery hospitalization were able to achieve pain relief similar to women not on MOUD but had higher MME requirements. Our results add to the emerging body of evidence suggesting that individuals on MOUD can achieve adequate post-surgical pain management without adjusting their pre-hospital dose of buprenorphine. Further research is required to fully understand the optimal buprenorphine dosing regimen during surgical hospitalizations. Our results also provide important preliminary evidence that spinal anesthesia containing opioids can be used effectively in individuals with OUD requiring surgical intervention.